2004
DOI: 10.1007/s00192-004-1248-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of the suprapubic arc sling procedure vs tension-free vaginal taping for stress incontinent women

Abstract: The purpose of this study was to compare the surgical outcome and attendant complications of the suprapubic arc (SPARC) sling and tension-free vaginal tape (TVT) procedures. Sixty-two women with genuine stress incontinence (GSI) alone or combined with pelvic prolapse less than International Continence Society (ICS) stage II were randomly allocated to either SPARC or TVT groups. A routine suprapubic ultrasonography was performed for all patients 1 day after the anti-incontinence operation. A comparison of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
4
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 10 publications
1
34
4
3
Order By: Relevance
“…Upon review of the literature, there is very little di¡erence between midurethral slings and TOT's with regard to postoperative DO and UUI in the majority of studies [Boustead, 2002;Davila et al, 2005;de Tayrac et al, 2005;Tseng et al, 2005]. With regards to urgency outcomes, two studies wary widely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon review of the literature, there is very little di¡erence between midurethral slings and TOT's with regard to postoperative DO and UUI in the majority of studies [Boustead, 2002;Davila et al, 2005;de Tayrac et al, 2005;Tseng et al, 2005]. With regards to urgency outcomes, two studies wary widely.…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of the TVT by Ulmsten and Petros [1995], Delorme [2001] has described a new approach to midurethral slings using the trans obturator route. These new procedures may have similar e⁄cacy rates to the retropubic midurethral slings in addition to decreasing complication rates related to bladder perforations and vascular injuries described with the retropubic midurethral slings [Wang et al, 2005].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There has been some controversy as to the comparable success rates when comparing the top-down vs. the bottom-up approach. There have been four randomized, prospective studies comparing the TVT sling (bottom-up) to the suprapubic arch (SPARC) sling (top-down) [9][10][11][12]. Three of the four studies showed equivalence of the TVT to the SPARC sling systems [9,10,12] with the longest follow-up at 25 months showing continence rates of 87% vs. 81%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There have been four randomized, prospective studies comparing the TVT sling (bottom-up) to the suprapubic arch (SPARC) sling (top-down) [9][10][11][12]. Three of the four studies showed equivalence of the TVT to the SPARC sling systems [9,10,12] with the longest follow-up at 25 months showing continence rates of 87% vs. 81%, respectively. [12] However, a study by Lord et al, which had the largest number of patients (147 TVT vs. 154 SPARC), showed superiority of the TVT over the SPARC with 87% vs. 77% success rates, respectively.…”
Section: Discussionmentioning
confidence: 99%